2010
DOI: 10.1111/j.1460-9568.2010.07161.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the persistence of contextual fear memories following immediate extinction

Abstract: Evidence suggests that extinction, the suppression of a learned response to a Pavlovian signal that is produced by exposure to the signal alone after conditioning, is a consequence of new inhibitory learning. However, it has been proposed that extinction given immediately after conditioning reflects memory 'erasure'. Using contextual fear conditioning, we examine the nature of extinction further using a novel behavioral paradigm that probes for the absence or presence of a memory. Rats received a context paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 29 publications
1
30
2
Order By: Relevance
“…In contrast to other studies using the CFC paradigm (e.g., Kimura et al 2008;Archbold et al 2010), we saw no spontaneous recovery of the behavioral performance after extinction training. Studies with fear conditioning to a discrete cue identified several factors that affect the resistance of extinction to recovery.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to other studies using the CFC paradigm (e.g., Kimura et al 2008;Archbold et al 2010), we saw no spontaneous recovery of the behavioral performance after extinction training. Studies with fear conditioning to a discrete cue identified several factors that affect the resistance of extinction to recovery.…”
Section: Discussioncontrasting
confidence: 54%
“…Studies with fear conditioning to a discrete cue identified several factors that affect the resistance of extinction to recovery. These include the interval between conditioning and extinction (Myers et al 2006;Woods and Bouton 2008;Huff et al 2009; but see Alvarez et al 2007;Schiller et al 2008;Archbold et al 2010), the interval between extinction and test (Bouton 1993(Bouton , 2004Quirk 2002), the level of fear behavior at extinction (Maren and Chang 2006), and the number and pattern of nonreinforced trails (Cain et al 2003;Urcelay et al 2009). These factors would be expected to interact with each other such that the precise experimental conditions used by independent laboratories would differentially reveal recovery of the cued fear responses.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study by Myers et al (2006) using fearpotentiated startle reported that extinction within a few minutes after acquisition (immediate extinction) caused a more durable suppression of the conditioned response than did extinction 24 h after acquisition. However, subsequent studies using aversive (Maren and Chang 2006;Woods and Bouton 2008;Chang and Maren 2009;Archbold et al 2010;Stafford et al 2013) and appetitive procedures (Rescorla 2004;Woods and Bouton 2008) in rodents as well as humans (Norrholm et al 2008;Schiller et al 2008) failed to observe superiority of immediate extinction. Indeed, in a number of studies immediate extinction was less effective than delayed extinction at suppressing the CR (Rescorla 2004;Maren and Chang 2006;Woods and Bouton 2008;Chang and Maren 2009;Stafford et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that cued and context fear conditioning recruit distinct neural mechanisms (Kim and Fanselow 1992;Phillips and LeDoux 1992;Maren et al 1997), raising the possibility that cued and context conditioning are differentially sensitive to immediate extinction. However, two recent studies (Archbold et al 2010;Stafford et al 2013) compared the effectiveness of immediate and delayed extinction of context fear and failed to observe superiority of immediate extinction. Thus, the use of contextual versus discrete-cue conditioning does not explain the differences between our findings and those studies failing to observe immediate extinction superiority.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in "extinction" (Pavlov 1927), CS-Shock pairings (the original association) are followed by CS-noShock presentations (the interfering association), and responding is consistent with the interfering association. However, retroactive interference wanes with time, and the original association once again comes to control behavior, a phenomenon known as "spontaneous recovery" (Pavlov 1927;Rescorla 2004a).According to recent reports, spontaneous recovery from extinction may be an inverse function of the original-interfering training (O-I) interval (Rescorla 2004b;Maren and Chang 2006;Woods and Bouton 2008;Chang and Maren 2009;Huff et al 2009;Johnson et al 2010; but see Myers et al 2006;Norrholm et al 2008;Schiller et al 2008;Archbold et al 2010;Johnson et al 2010). However, why delaying extinction reduces spontaneous recovery is not fully understood.…”
mentioning
confidence: 99%